368. EARLY DELAYED GASTRIC EMPTYING AFTER ESOPHAGECTOMY: VALIDATION OF THE INTERNATIONAL EXPERT CONSENSUS DEFINITION (MIE GROUP). (24th September 2022) - Abdelrahman, Mohamed; Fu, Kathryn; Tham, Ji; Emslie, Katy; Ariyarathenam, Arun; Berrisford, Richard; Humphreys, Lee; Sanders, Grant; Wheatley, Tim; Chan, David
Abstract: Early delayed gastric emptying (DGE) affects up to 37% of patients after esophagectomy. An international expert consensus (IEC) agreed on a diagnostic criteria in 2020. The degree of adoption of this definition worldwide is unknown and how it compares to well established definitions locally with subtle yet significant differences. The aim of this study was to compare the IEC definition of early DGE to the definition at the University. All patients who underwent esophagectomy for cancer at UHP between April 2019–August 2020 were analysed. The IEC definition was applied retrospectively and the rates of DGE were compared between the two criteria. One hundred consecutive patients [74 Male (74%), median age (range) 68 (45–83 years)] were analysed. The rates of early DGE according to the IEC and UHP definitions were 20% and 28% respectively (p = 0.246). Eight patients had anastomotic leak, 6 of whom had DGE. Pneumonia was diagnosed in 28 patients (8 and 6 in the IEC and UHP groups respectively). Twenty-nine patients (29%) had pyloric balloon dilatation (PBD). Seventeen patients in the index admission and twelve at later date. Of the 17 patients 9 were in the IEC group and 11 in the UHP group. The UHP definition does seem to match the MIE consensus definition and is not inferior. The dynamic process of DGE does support the policy our unit has to continue monitoring patients with chest radiographs. This not only identifies DGE early and modify management but also allows assessment of conduit after the patient starts eating. Definition of Early Delayed Gastric Emptying post Esophagectomy.pdf (could not be inserted).